2008
DOI: 10.1038/nn.2222
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine in amygdala gates limbic processing of aversive stimuli in humans

Abstract: Dopamine is released under stress and modulates processing of aversive stimuli. We found that dopamine storage capacity in human amygdala, measured with 6-[ 18 F]fluoro-L-DOPA positron emission tomography, was positively correlated with functional magnetic resonance imaging blood oxygen leveldependent signal changes in amygdala and dorsal anterior cingulate cortex that were evoked by aversive stimuli. Furthermore, functional connectivity between these two regions was inversely related to trait anxiety. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 156 publications
(116 citation statements)
references
References 15 publications
8
103
1
4
Order By: Relevance
“…We found that DA D1 receptors, but not D2 receptors, predicted amygdala response induced by novel facial stimuli with either neutral or fearful expression. Our findings broaden our knowledge about dopaminergic transmission in amygdala response beyond the recent study (Kienast et al, 2008) that elucidated the relation between presynaptic dopamine synthesis and amygdala reactivity.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We found that DA D1 receptors, but not D2 receptors, predicted amygdala response induced by novel facial stimuli with either neutral or fearful expression. Our findings broaden our knowledge about dopaminergic transmission in amygdala response beyond the recent study (Kienast et al, 2008) that elucidated the relation between presynaptic dopamine synthesis and amygdala reactivity.…”
Section: Discussionmentioning
confidence: 51%
“…In addition, another fMRI study of healthy volunteers has demonstrated that amphetamine potentiated the response of the amygdala during an emotional task . More recently, Kienast et al (2008) reported that dopamine storage capacity in human amygdala, measured with 6-[…”
Section: Introductionmentioning
confidence: 99%
“…fMRI paradigms. FMT based on emotion identity recognition, this task, originally developed by Hariri et al (2000), has been widely used by our group and others (Hariri et al, 2002;Kienast et al, 2008) and has been shown to strongly engage the amygdala and HF. The subjects underwent two experimental conditions: emotional identity face matching and a sensorimotor task.…”
Section: Subjectsmentioning
confidence: 99%
“…There are also strong anatomical connections between rostral parts of ACC and other limbic structures involved in affect and motivation, such as the amygdala and insula (van Hoesen, Morecraft, & Vogt, 1993;Ongur & Price, 2000; see also Ochsner & Gross, 2005;Kienast et al, 2008). Based on this evidence, some theories proposed that ACC activity following errors could also reflect an appraisal of the affective significance or salience of errors (Luu, Tucker, Derryberry, Reed, & Poulsen, 2003;Hajcak, Moser, Yeung, & Simons, 2005;Pizzagalli, Peccoralo, Davidson, & Cohen, 2006;Taylor et al, 2006;Polli et al, 2008Polli et al, , 2009Li et al, 2008;Hajcak & Foti, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Further, in a recent scalp ERP study in healthy participants, Hajcak & Foti (2008) found that the startle blink reflex was enhanced following errors during a flanker task, suggesting that error monitoring could also activate the defensive motivational system responsible for the startle reflex (Lang, Bradley, & Cuthbert, 1990). Because both the amygdala and insula are implicated in anxiety and defensive behaviors, these limbic regions might also contribute to error detection processes taking place in dorsal ACC (Ochsner & Gross, 2005;Fales et al, 2008;Kienast et al, 2008). Indirect evidence in support of this theory comes from a few neuroimaging studies that showed increased activity to errors not only in ACC and PFC, but also in deeper limbic brain structures such as the amygdala, insula, and thalamus (Menon, Adleman, White, Glover, & Reiss, 2001;Garavan, Ross, Murphy, Roche, & Stein, 2002;Polli et al, 2008;Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%